Study on regional differences and causes of emergency logistics responsiveness under the impact of public emergencies—findings from Chinese samples - Chen, Heng; Guo, Yuan; Lin, Xianglong; Qi, Xianchao (Frontiers in Public Health, 2024)
IntroductionIn recent years, the frequency and intensity of natural disasters and public emergencies around the world have been steadily increasing. Emergency logistics plays an irreplaceable role in providing rapid material and service support in the aftermath of disasters. Therefore, systematically analyzing the differences in emergency logistics responsiveness across various regions of China and understanding their underlying causes are of great significance for optimizing emergency logistics systems and improving disaster responsiveness.MethodsIn order to identify the regional differences and causes of China’s emergency logistics responsiveness under the impact of public emergencies, this paper pioneered the development of an index system for evaluating emergency logistics responsiveness. Based on the panel data of 30 provinces in China from 2012 to 2021, this paper used the entropy-weighted TOPSIS method to quantify the emergency logistics responsiveness of various regions in China. In addition, this study uses a panel quantile regression model to evaluate the differences in emergency logistics responsiveness in various regions of China under the impact of public emergencies, and the causes of regional differences are explored.ResultsThe research results show that: (1) China’s emergency logistics responsiveness is upward, but the regional differences are expanding. (2) Compared with the central and eastern regions, the western region’s emergency logistics responsiveness has continuously improved due to the expanding scale of public emergencies. However, the emergency logistics responsiveness of the eastern region has constantly been reduced due to the impact of public emergencies. In contrast, the central region has been reduced first and then improved. (3) The level of emergency logistics technology cannot effectively promote emergency logistics responsiveness. Under the impact of public emergencies, the labor input of the logistics industry cannot effectively meet the needs of emergency logistics activities. The administrative command method and the level of marketization inhibit emergency logistics responsiveness. The improvement of the social labor input level, urbanization level, logistics development level, and digitalization level can effectively promote emergency logistics responsiveness.DiscussionThe above results show that China should pay attention to regional differences. Each region should rely on the existing logistics system and plan and build emergency logistics hubs according to the characteristics of emergencies in each region. Continue to strengthen regional exchanges and cooperation to narrow the gap in regional emergency logistics responsiveness. At the same time, this paper plays a driving role in China’s joint emergency logistics rescue cooperation with other countries worldwide.